昭和基地におけるEXOS-A(極光)の受信 - 福西, 浩; フクニシ, ヒロシ; Fukunishi, Hiroshi; 岩渕, 美代子; イワブチ, ミヨコ; Iwabuchi, Miyoko; 芳野, 赳夫; ヨシノ, タケオ; Yoshino, Takeo (国立極地研究所, 1978)
1978年2月4日16時00分東京大学鹿児島宇宙空間観測所より打ち上げられた日本初の極軌道科学衛星EXOS-A(極光)の受信は,現在鹿児島,カナダのチャーチル,南極昭和基地の3ヵ所で行われている.この報告では昭和基地での受信状況について詳しく述べる. Telemetry signals from the first Japanese polarorbitting satellite, EXOS-A (Kyokko) are being received at three satellite acqusition stations, i.e., Kagoshima, Churchill and Syowa Satellite Earth Stations. In this report, the progress of the data acqusition at Syowa is described. departmental bulletin paper